Environmental awareness and education: a key approach to solid waste management (swm) - a case study of Klang valley - Tajuddin, Husna Ahmad; Ridwan, Muhammad Afiq; Mansor, Mariatul Fadzillah (IIUM, 2021)
Solid waste management has been a worldwide issue which most countries are finding the best ways to deal with it. Improper waste management poses a threat to the health of individuals and the environment. The general problem is the perception of the local communities towards solid waste management. It is important to analyze the current level of awareness towards solid waste management to be serve as reference for policy making or education purposes. Thus, this research seeks to analyze the level of awareness towards solid waste management in Klang Valley, which is defined into three aspects knowledge, attitude, and behavior. This research is described as a descriptive survey that is done on Klang Valley communities. The statistical analysis used in this research are descriptive, frequency and Principal Component Analysis using Statistical Packages for Social Science (SPSS) Software for statistical analysis. Generally, regarding solid waste management in Klang Valley, the respondents are highly knowledgeable except for e- waste, however the calculated mean for the attitude is 1.85 and 2.66 for behavior which indicates that their level of attitude and behavior towards solid waste management is low and moderate. Principal component analysis shows that there are three and four principal components for attitude and behavior sections respectively which greatly impact on the respondent’s attitude and behavior towards solid waste management. To conclude, promotional and encouragement on proper solid waste management has to be conduct frequently by the public or authorities.